(untitled) (Texas Journal of Medical Science, 2023)
One of the most common surgical pathologies are external abdominal hernias. The share of postoperative ventral hernias (POVH) accounts for up to 15-18% of the total number of patients with abdominal hernias. More than 1.5 million surgical interventions for ventral hernias are performed annually in the world, in the CIS countries this figure exceeds 200,000 operations. Modern studies have shown that the surgical treatment of patients with POVH should be based on a personalized approach, taking into account the existing concomitant pathologies, risk factors, surgical potential of the operating go doctor and hospital.